2022
DOI: 10.1101/2022.10.07.511369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discovery of deep-sea coral symbionts from a novel family of marine bacteria, Oceanoplasmataceae, with severely reduced genomes

Abstract: In addition to abundant animal communities, corals from all ocean depths support diverse microbial associates that are important to coral health. While some of these microbes have been classified taxonomically, understanding the metabolic potential of coral-associated bacteria and how they interact with their coral hosts is limited by a lack of genomic data. One example is Mycoplasma and other members of the class Mollicutes which are widespread coral associates. Here we investigated the association between tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 115 publications
0
4
0
Order By: Relevance
“…The alternative explanation, that C. delta was supplemented with chemosynthetically fixed carbon from a bacterial symbiont living within its tissue, was less likely for three reasons. (i) The assembled whole genome of Mollicutes (i.e., the dominant bacterial phylotype, see Figure 3 ) collected from some of the C. delta colonies used in the current study showed lack of chemosynthetic pathways (Vohsen et al, 2022 ). (ii) The relative abundances of C. delta dominant symbiotic bacteria (i.e., Mollicutes—Figure 3 ) were not significantly different between seep and non‐seep samples and did not correlate with stable isotope values (Figure S6 ).…”
Section: Discussionmentioning
confidence: 89%
“…The alternative explanation, that C. delta was supplemented with chemosynthetically fixed carbon from a bacterial symbiont living within its tissue, was less likely for three reasons. (i) The assembled whole genome of Mollicutes (i.e., the dominant bacterial phylotype, see Figure 3 ) collected from some of the C. delta colonies used in the current study showed lack of chemosynthetic pathways (Vohsen et al, 2022 ). (ii) The relative abundances of C. delta dominant symbiotic bacteria (i.e., Mollicutes—Figure 3 ) were not significantly different between seep and non‐seep samples and did not correlate with stable isotope values (Figure S6 ).…”
Section: Discussionmentioning
confidence: 89%
“…Both C. delta and P. biscaya hosted three dominant ASVs. All three dominant ASVs in C. delta were recently described [29] as novel members of the class Mollicutes: two Ca. Oceanoplasma and one Ca.…”
Section: Resultsmentioning
confidence: 99%
“…and possess capabilities relevant to the coral host such as producing vitamins [25, 26], degrading dimethylsulfoniopropionate [27], and cycling phosphorus [28]. Similarly, corallicolid apicomplexans and Mycoplasma are commonly found in many coral species and reside within or on coral tissue [10, 18, 29]. Most apicomplexans [30] and Mycoplasma spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation